Gravity anomaly to identify Walanae fault using second vertical derivative method - Marsellei Justia; Muhammad Fikri H Hiola; Nur Baiti Febryana S (Universitas Sebelas Maret, 2018)
Research has been conducted to identify the Walanae Fault, coordinates 4–6 S and 118-120 E using anomalous gravity data. This research uses data measurement of Topography and the Free Air Anomaly from the TOPEX/Poseidon satellite. Then the authors processed to obtain the bouguer anomalies and made modeling by using the Surfer 10. The authors used the Second Vertical Derivative (SVD) with filter Elkins of Moving Average then analyze the graph of the SVD. The results shows the value of the residual anomaly in the north of fault is 25.21 mGal, in the middle occur range 17.67 mGal to 24.98 mGal and 30,376 mGal in the south of fault. The authors indicates the existence of a difference between the gravity between the Walanae Fault with surrounding geologic. From these results also show that Walanae Fault has a reverse fault mechanism in the northern part and the normal fault mechanism in the middle to the south, the authors conclude that the Walanae Fault is divided into two segments, that is the northern and the southern segment.